New Stability Criteria for Event-Triggered Nonlinear Networked Control System with Time Delay - Hongqian Lu; Yue Hu; Chaoqun Guo; Wuneng Zhou (Complexity)
This note focuses on the stability and stabilization problem of nonlinear networked control system with time delay. To alleviate the burden of transformation channel and shorten the dynamic process simultaneously, an improved event-triggered scheme is proposed. This paper employs an improved time delay method to enhance the performance and reduce the delay upper bound conservatism. Less conservative stability criteria related to the order N are derived by establishing an augmented Lyapunov-Krasovskii functional manufactured for the use of Bessel-Legendre inequality. In addition, an event-triggered controller is designed for nonlinear networked control system with time delay. At last, numerical examples are proposed to verify the effectiveness of the new method.